1989
DOI: 10.1007/bf01870852
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gating of a metabolically regulated, ATP-dependent K+ channel by intracellular pH in B cells of the pancreatic islet

Abstract: Membrane-permeant weak acids and bases, when applied to the bath, modulate the resting membrane potential and the glucose-induced electrical activity of pancreatic B cells, as well as their insulin secretion. These substances alter the activity of a metabolite-regulated, ATP-sensitive K+ channel which underlies the B-cell resting potential. We now present several lines of evidence indicating that the channel may be directly gated by pHi. (1) The time course of K+(ATP) channel activity during exposure to and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 18 publications
1
30
2
Order By: Relevance
“…In fact, studies of excised patches of cardiomyocyte (52) or ␤-cell (53) membranes have shown that micromolar concentrations of amiloride and derivatives can directly inhibit K ATP channels by interacting with the pore. Our results do not rule out the possibility that changes in pH c can influence K ATP channels in ␤-cells (54,55), but preclude the use of amiloride derivatives to test the role of Na ϩ /H ϩ exchange itself and of pH c changes in insulin secretion. We therefore used two other approaches: the NHE1 mutant islets and the direct comparison of insulin secretion and pH c changes in HCO 3 Ϫ and HEPES media.…”
Section: Nhe1 and Islet Cell Ph C Regulation-nacontrasting
confidence: 58%
“…In fact, studies of excised patches of cardiomyocyte (52) or ␤-cell (53) membranes have shown that micromolar concentrations of amiloride and derivatives can directly inhibit K ATP channels by interacting with the pore. Our results do not rule out the possibility that changes in pH c can influence K ATP channels in ␤-cells (54,55), but preclude the use of amiloride derivatives to test the role of Na ϩ /H ϩ exchange itself and of pH c changes in insulin secretion. We therefore used two other approaches: the NHE1 mutant islets and the direct comparison of insulin secretion and pH c changes in HCO 3 Ϫ and HEPES media.…”
Section: Nhe1 and Islet Cell Ph C Regulation-nacontrasting
confidence: 58%
“…This may be due to the GA-induced drop in pH i , which may have effects such as closure of K ATP channels (48,51,52), inhibition of gap junctional conductance (53) (which may be important for electrical coupling to promote oscillatory behavior), and inhibition of PFK-M, the putative generator of the oscillations, because the enzyme has been shown to be extremely pH-sensitive (53,54). Indeed, we previously showed in the glycolyzing muscle extract system that differences in the initial pH of 0.1 unit or less could greatly affect the time of initiation and the period of the oscillations (55).…”
Section: Dihydroxyacetone and Ca 2ϩ Oscillations 40714mentioning
confidence: 99%
“…It should be remembered, however, glucose-stimulated insulin secretion [8][9][10][11]. The inhibition of K ATP channels is a possible mechanism of the intracellular acidic pH effect on insulin secretion [12]; K ATP channels have histidine residues involved in either the inhibition or the activation of the activity in response to a change in the intracellular pH [13,14]. The beneficial role of acidic pH on insulin secretion is supposed to be mainly based on the action of the Na + / H + exchange blocker: inhibitors of Na + /H + exchange caused the enhancement of glucose-stimulated insulin secretion in association with a decrease in the intracellular pH.…”
Section: Proton-sensing Ion Channelsmentioning
confidence: 99%
“…In order to evaluate the role of ability to inhibit K ATP channels and, thereby, to induce depolarization of the cells [12,14]. OGR1 deficiency inhibited insulin secretion at neutral pH 7.4, suggesting that OGR1 is functioning at a physiological pH.…”
Section: In Vivo Analysismentioning
confidence: 99%